PELANGGARAN PRINSIP KERJA SAMA PADA DIALOG ANTARTOKOH DALAM NOVEL KOALA KUMAL KARYA RADITYA DIKA - Erlik Fauziyah; Syamsul Ghufron (EDU-KATA, 2020)
This study aims to describe the types of violations of the principle of cooperation in dialogue between groups in the novel Koala Kumal by Raditya Dika. This study used descriptive qualitative method. The data source of this research is Raditya Dika's Koala Kumal novel which consists of 12 stories. Data collectiontechniques used include techniques for reading, listening, and taking notes. The research instrument used was a cooperative principle indicator in the form of a table. Data analysis techniques with qualitative descriptive methods with steps to collect data, data reduction, data presentation, and drawing conclusions. The results of this study show two conclusions. First, the form of violation of the principle of cooperation that occurs is (1) the maxim of quantity, (2) the maxim of quality, (3) the maxim of relevance, and (4) the maxim of the method or implementation. Second, namely the three objectives of violating the principle of cooperation, namely (1) representative purpose: providing information or giving explanations, ensuring, expressing expectations, and affirming, (2) directive objectives: insinuating, mocking, giving advice, and criticizing or protesting, and (3) expressive goals: lying, boasting, expressing dislike, expressing concern, seducing or teasing, praising, confused, and creating humor.